Notes on Catulona Rolston, 1992, and the description of a newspecies from Brazil (Hemiptera, Pentatomidae, Discocephalinae) - Campos, Luiz Alexandre; Grazia, Jocélia; Greve, Caroline (Zootaxa, 2004)
Catulona Rolston, 1992 was described for two species, the type species Catulona pensa Rolston and Catulona apaga Rolston, both from southeastern and southern Brazil. Here Catulona lucida Campos & Grazia, sp. nov. is described from southeastern Brazil, and contributions to the description of Catulona, C. pensa, and C. apaga are made. Male and female genitalia are described for the genus and described and illustrated for C. lucida. Parameres and phallus of C. pensa are also described. The collection of the American Museum of Natural History is assigned as the new deposit site to the holotype of C. pensa. New geographical data are given.